Spindle-Shaped Surface Microstructure Inspired by Directional Water Collection Biosystems to Enhance Interfacial Wetting and Bonding Strength - Wan, Hailang; Min, Junying; Carlson, Blair E; Lin, Jianping; Sun, Chengcheng (ACS applied materials & interfaces, 2021)
Unique spindle microstructures with an apex angle of ∼20° bring the ability of directional water collection to various biosystems (i.e., spider silk and cactus stem). This has great potential to solve the insufficient interfacial wetting for mechanical interlocking formation between polymers and substrates. In this study, the bioinspired spindle microstructures were easily fabricated through the deposition of molten materials by a nanosecond laser with an overlap ratio of 21% between laser spots and achieved superior interfacial wetting for commercial epoxy adhesive on aluminum substrates. Detailed analyses show that there are four mechanisms responsible for the superior interfacial wettability of bioinspired spindle microstructures: the Laplace pressure difference, newly formed aluminum oxide, the capillary effect, and no extra pressure from a trapped atmosphere. Consequently, the bioinspired spindle surface microstructures achieve a maximum improvement of ∼16 and ∼39% in interfacial bonding strength before and after water soak exposure compared to the as-received condition. Moreover, the stable interfacial wettability of bioinspired spindle microstructures ensures that the improved joint strength varied little with an increase in surface roughness from ∼1.7 to ∼12.8 μm. However, the interfacial wettability of common dimple microstructures deteriorated with an increase in surface roughness, which is indicated by the decreasing rule in the quadratic polynomial function of the interfacial bonding strength as the surface roughness increases from ∼2.1 to ∼18.2 μm.